Multiple layered anti-counterfeit lables - Yuan, Jing (2018)
Shape memory polymers are polymeric materials that have shape recovery ability, they are able to return to the original shape under different kinds of stimulus like heat. SMP can be used in many areas, multiple layered anti-counterfeit labels is one of the applications. To make the security label, the first step is to compress the SMP film at high temperature to get the permanent deformation. The second step is to recompress the SMP film at a lower temperature to get the temporary deformation, so the permanent deformation can be covered or hided. Upon heat stimulus, the second compression pattern will disappear, thus the hided permanent deformation will become clear and visible. Material selection, compression temperature and mould design are the 3 key factors that need to be considered in this project. Different kinds of SMP are tested under heat stimulus. Some improvements on the mould design are also made to reduce stress whitening effect.